Performing historiography: knowledge framed by scenical language (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article is part of a broader research on the types of knowledge supported by Performing Arts. It investigates how history and historiography can be understood when observed through the frame of theatrical language. Through the analysis of the piece Derretiré con un cerillo la nieve de un volcán (2013), by the Mexican group Lagartijas Tiradas al Sol, subjective, processual, embodied and territorializing dimensions that involve the scenic gesture of historiography are highlighted.
Keywords: performing arts; historiography; knowledge